2016
DOI: 10.3390/ani6020012
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Understanding of Psychological Factors Contributing to Horse-Related Accident and Injury: Context, Loss of Focus, Cognitive Errors and Rigidity

Abstract: Simple SummaryThere is a high risk of injury for people involved with horses in their work or recreational pursuits. High risks are particularly evident for racing employees and veterinarians. Elevated risks of injury may be associated with misjudging how to handle situations, reduced attention caused by distractions, taking a general view, and failing to consider other strategies that may reduce risks. To improve safety for humans and horses, it is important to identify safety strategies that are flexible, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Traumatic injuries during transportation may involve also horse handlers. An elevated risk of injury has been associated with poor experience, misjudging how to handle a situation, reduced attention caused by distraction, taking a general view, and failing to consider other strategies that may reduce risks [ 39 ]. To improve safety for humans and horses, knowledge and experience in horse handling and driving would appear important.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic injuries during transportation may involve also horse handlers. An elevated risk of injury has been associated with poor experience, misjudging how to handle a situation, reduced attention caused by distraction, taking a general view, and failing to consider other strategies that may reduce risks [ 39 ]. To improve safety for humans and horses, knowledge and experience in horse handling and driving would appear important.…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to horse handlers lacking a perception/understanding/appreciation of the importance of training horses for travel (almost half of the survey respondents reported that they did not train their horses for travelling [ 41 , 43 ]) or to the use of inappropriate training methods [ 1 , 41 ]. Insufficient knowledge of how to manage horse-related situations has been associated with elevated risk of horse-related accidents [ 8 ].…”
Section: Trpbs: Current Knowledge Definitions Causes and Consequenmentioning
confidence: 99%
“…Caution should also be exercised when interpreting hospital-or registry-based data and relying upon them for estimates of risks because, as found in our study and others, many injuries are either not treated or medical assistance is not sought [46]. This behaviour may be a manifestation of the normalisation of risk in equestrian culture and/or the acceptance that horse-related activities such as riding are high risk, both of which have been considered obstacles to improving equine-related safety [2,14,38,47].…”
Section: Discussionmentioning
confidence: 69%
“…However, pony club and equestrian and racing qualifications have many similarities in New Zealand, Australia, and the United Kingdom based on a shared colonial history. The increased odds of injury associated with higher levels of qualification are most likely reflective of those more frequently engaged in industry activities and, therefore, at greater cumulative exposure to the risk in associated competitive equestrian activities or equine industry work environments [30,38]. The association of a decrease in risk of injury with driver experience (2% per year) was not found for equine injury in a companion paper [30].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation